QUALITY OF LIFE IN NON-SMALL CELL LUNG CANCER PATIENTS WITH BRAIN METASTASES AFTER TREATMENT WITH A COMBINATION OF GAMMA KNIFE RADIOSURGERY AND TKIs (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the changes in quality of life (QoL) in non-small cell lung cancer (NSCLC) patients with brain metastases after treatment with a combination of Gamma Knife radiosurgery and TKIs.Subjects and methods: A longitudinal, prospective descriptive study was conducted on 43 NSCLC patients with brain metastases who received Gamma Knife radiosurgery combined with TKIs from January 2023 to December 2024.Results: At the 6-month follow-up, most aspects of QoL remained stable. Several functions and symptoms showed significant improvement, such as: emotional function, fatigue, insomnia, future uncertainty, and motor dysfunction (improvement > 10 points, p
Keywords: Quality of life, Gamma Knife radiosurgery, TKIs, NSCLC, brain metastases.